The genus Kretzschmaria from Tucumán, Argentina - Hladki, Adriana Ines (2001)
Six taxa of Kretschmaria - including those taxa formerly considered as Ustulina - from Argentina are described and included in keys. Two new species, Kretzschmaria argentinensis and K. sigmoidirima, are proposed. K. deusta, K. sandvicensis and K. parvimentosa are first records from Argentina. The distribution area in Argentina of K. clavus is enlarged.